2003
DOI: 10.2134/agronj2003.1172
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effects of Legumes with Rock Phosphorus on Rice in West Africa

Abstract: from the soil where little or no external inputs are applied. The depletion in essential plant nutrients of the Rice (Oryza sativa L.) demand in West Africa is unmet because of predominantly sandy Alfisols and Ultisols of the region insufficient production. Legume fixed N [biological N fixation (BNF)] may sustainably increase rice productivity in low-input systems. How-is seen as a major threat to the sustainability of smallever, P deficiency limits BNF on the acid soils encountered in the holder production sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
2
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 29 publications
1
23
2
1
Order By: Relevance
“…In SW Niger many studies have been conducted on how to alleviate the notoriously low P status of the dominant acid sandy soils (Bationo and Mokwunye 1991;Kretzschmar et al 1991;Buerkert et al 1998;Buerkert et al 2001;Somado et al 2003). While Squalli and Nadir (1983) suggested the use of soluble superphosphate for arid Moroccan market gardens, in Niamey the locally available inexpensive Tahoua RP (costs were 0.5 € per 10 kg in 2007) of which high agronomic efficiencies for on-farm millet fields were previously reported by Bationo et al (1990), might present an effective way of increasing garden soil P stocks while decreasing N losses during dung storage.…”
Section: Discussionmentioning
confidence: 99%
“…In SW Niger many studies have been conducted on how to alleviate the notoriously low P status of the dominant acid sandy soils (Bationo and Mokwunye 1991;Kretzschmar et al 1991;Buerkert et al 1998;Buerkert et al 2001;Somado et al 2003). While Squalli and Nadir (1983) suggested the use of soluble superphosphate for arid Moroccan market gardens, in Niamey the locally available inexpensive Tahoua RP (costs were 0.5 € per 10 kg in 2007) of which high agronomic efficiencies for on-farm millet fields were previously reported by Bationo et al (1990), might present an effective way of increasing garden soil P stocks while decreasing N losses during dung storage.…”
Section: Discussionmentioning
confidence: 99%
“…La riziculture pluviale en Afrique de l'Ouest souffre de l'acidite´des sols en de´pit des travaux re´alise´s sur la fertilisation en P (Sahrawat et al 1995 ;Somado et al 2003). Ainsi, les rendements de´passent rarement 1,5 t ha…”
unclassified
“…Many researchers mentioned that PR application as P source with inoculation of Rhizobium was able to increase the performance of legume. Somado et al (2003) observed that in both the pot and field experiments, there was a significant response of legume performance to PR application. Alfalfa responsed to P fertilizer application in latosol soil.…”
Section: Alfalfa Production Used Different P Fertilizersmentioning
confidence: 84%